2012
DOI: 10.1007/s13224-012-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Pregnancy Outcomes in Nulliparous Women Delivering Singleton Babies: Observational Study

Abstract: Objective To find out the effect of increasing body mass index (BMI) on pregnancy outcomes in nulliparous women delivering singleton babies. Conclusions Increasing BMI is associated with increased incidence of cesarean delivery, PIH, post partum hemorrhage, and macrosomic babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
0
23
0
3
Order By: Relevance
“…However, these studies did not adjust the results for BMI, whereas we did. Increased BMI has been associated with a higher risk of postpartum haemorrhage for nulliparous women [49] and women with high BMI were more likely to give birth in hospital in our study.…”
Section: Discussionmentioning
confidence: 52%
“…However, these studies did not adjust the results for BMI, whereas we did. Increased BMI has been associated with a higher risk of postpartum haemorrhage for nulliparous women [49] and women with high BMI were more likely to give birth in hospital in our study.…”
Section: Discussionmentioning
confidence: 52%
“…The present study demonstrated that no significant differences occurred in the PIH rate between women with type 1 and type 2 DM. Even in normal glucose-tolerant women and those with gestational diabetes, maternal BMI is an independent risk factor for PIH [18,19]. Moreover, along with maternal pregestational BMI, the presence of diabetic microangiopathy, including retinopathy or nephropathy, in type 1 DM has also been previously reported as a risk factor for PIH [20].…”
Section: Resultsmentioning
confidence: 97%
“…El estudio muestra que un IMC pregestacional correspondiente a bajo peso es un factor de riesgo para el Bajo Peso al Nacer y PEG, tal como se ha reportado en otros trabajos 18,19,20 . Por ejemplo, en un estudio publicado en el 2016, el cual reclutó 1,336 gestantes japonesas, encontró que las que presentaban IMC bajo, presentaron un OR de 1.86 (1.04-1.31) frente a las que presentaron IMC no rm al 21 , similar a nuestro resultado.…”
Section: Discussionunclassified
“…Por otro lado, se obtiene que el sobrepeso es un factor protector, mientras que la obesidad no resulta significativa, aunque con tendencia a ser protector; no obstante, si bien el riesgo de Bajo Peso al Nacer es menor con IMC pregestacional elevado, esto puede ser de igual manera perjudicial, dado que el recién nacido tiene una mayor probabilidad de resultar macrosómico 18 , el cual es un factor importante de morbilidad materno-perinatal [22][23] .…”
Section: Discussionunclassified